2014
DOI: 10.1149/2.0821410jes
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroplating Additives on the Interfacial Reactions between Sn and Cu Electroplated Layers

Abstract: Three combinations of additives based on polyethylene glycol (PEG), Cl − ions, bis(3-sulfopropyl)disulfide (SPS), and Alcian Blue (ABPV) were used to fabricate the Cu plated layer. The additive combination was found to play an important role in the microstructural evolution of the Cu plated layer. The PC (PEG + Cl − ) case produced the Cu plated layer with grains of a smaller size and random morphology, while the PCS (PEG + Cl − + SPS) and PCSA (PEG + Cl − + SPS + ABPV) cases produced the Cu plated layers with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
(45 reference statements)
1
20
0
Order By: Relevance
“…Wu et al [30] found that the addition of only suppressor (PEG + Cl − ) in the plating bath originally containing basic electrolyte (H 2 SO 4 and CuSO 4 ) resulted in a high level of impurity incorporation in the electroplated Cu layer. Addition of accelerator (SPS), together with the suppressor, remarkably reduced the impurity concentration by two orders of magnitude.…”
Section: Effects Of Plating Parameter and Additive Formula On Impuritmentioning
confidence: 99%
See 3 more Smart Citations
“…Wu et al [30] found that the addition of only suppressor (PEG + Cl − ) in the plating bath originally containing basic electrolyte (H 2 SO 4 and CuSO 4 ) resulted in a high level of impurity incorporation in the electroplated Cu layer. Addition of accelerator (SPS), together with the suppressor, remarkably reduced the impurity concentration by two orders of magnitude.…”
Section: Effects Of Plating Parameter and Additive Formula On Impuritmentioning
confidence: 99%
“…Recently, our group published a series of papers exploring the effects of additive formulas on the impurity level in the Cu-plated layer and the interfacial reactions in the Sn/Cu joints [18,30,31]. First, three additive formulas were tested including PC, PCS, and PCSA (A is an abbreviation of leveler "ABPV") with a plating current density of 32 A/ft 2 (34.44 mA/cm 2 ) [30].…”
Section: Effects Of Impurity On Interfacial Reactions Of Electroplatementioning
confidence: 99%
See 2 more Smart Citations
“…The impurities incorporated in the Cu lms played the roles to produce plenty of vacancies nucleating at the SAC305/Cu C interface. Segregation of the impure species or their derivatives in the grain boundaries might also annihilate the vacancy sinking sites which accelerated the accumulation of vacancies to form voids [14][15][16]. Severe void propagation gave rise to the formation of continuous crevices or cracks which was a kind of volumetric defects in crystal caused by void nucleation during annealing [17,18].…”
Section: Resultsmentioning
confidence: 99%